AICCRA Zambia Cluster Participation at the 97th National Agricultural and Commercial Show - Chikoye, D.; Makungwe, Mirriam; Kasoma-Pele, Winnie; Nali, R.; Mulundu, S.; Sibeso, C (2025)
AICCRA Zambia participated in the 97th National Agricultural and Commercial Show, held from July 29 to August 3, 2025, at the Lusaka Showgrounds. This year’s event was hosted under the national theme “Adapting to Climate Change.” Over 150 farmers visited the AICCRA stand and the event provided an opportunity to educate them on the adoption of validated CSA technologies and enhanced CIS advisories, including information on where farmers can access these technologies. The main CSA practices promoted during the show included minimum tillage to preserve soil structure and improve soil health, mulching to conserve moisture and reduce erosion, and crop diversification to spread production risks and enhance farm productivity. The AICCRA team also emphasised the importance of weather-indexed and crop insurance schemes as financial safety nets to help farmers recover quickly from climate-related shocks. Other showcased innovations included solar-powered irrigation systems, such as smart drip irrigation technologies that deliver water directly to plant roots with minimal waste, as well as integrated aquaculture–agriculture systems—models designed to optimise resource use within a single farm.